Proposal and Validation of Scale for Tourist Capacity Measurement - Silveira-Martins, Elvis; Zonatto, Vinícius Costa da Silva (Revista Turismo em Análise, 2015)
This study aims to develop and validate a scale to measure the tourism capacity of companies operating in this segment. Tourist capabilities discussed in this work are understood as the capacity of organizations working in the tourism sector in managing internal potential of the company with a view to adding value to the services provided. Through these, it becomes possible to differentiate and develop competitive advantages as well as strengthening those organizations. Therefore, exploratory and descriptive research was conducted with 65 hotels focused on tourism, located in different regions of São Paulo. The results showed the five determinants tourist capacities for competitive differentiation of these companies, which make up the proposed construct in this study, which are: generation of personalized service to tourists; knowledge about the tourist attractions (local) in the city and region; attention to new tourism events (local) in the city and region; knowledge of the local and regional history; and location close to strategic points. It is concluded that the understanding of the tourist capacities developed for hotel companies can contribute to the understanding of factors that favor the adaptive capacity of these companies considering the characteristics of the dynamic environment. Similarly, can provide evidence to the understanding of how these companies achieve and sustain competitive advantages, resulting in a new field of research for this topic.